Analysis of the Accounting Information System for Employee Payroll of the Makassar City Regional Representative Council - Halmi; Sri Rahayu Syah; Julkifli; Muh. Imaduddin (Academic Bright Collaboration, 2025)
This research aims to analyze the implementation of the Employe Payroll Accounting Information System (AIS) at the Secretariat of the Regional People's Representative Council of Makassar City. This research uses a descriptive qualitative approach. Data were collected thru observation, documentation, and in-depth interviews with key informants selected using the snowball sampling technique. Data analysis involved data collection, data reduction, data presentation, and drawing conclusions. The validity of the findings was checked using source triangulation and method triangulation. The research results confirm that the Payroll Accounting Information System of the Makassar City Regional People's Representative Council is adequate thru the utilization of the SIMAKDA system (for employes) and SIPGAJIDEWA system (for council members). The findings show that both systems automatically generate 100% of the required documents, including the Payroll List, Tax Deduction Recapitulation, and Non-Tax Deposit Letter. The system's advantage lies in the integration of automation formats that ensure the accuracy of financial data and compliance with public sector tax regulations in real-time. This research only focuses on the functional and administrative analysis of the system at one location, so the generalization of the findings may be limited to agencies with similar bureaucratic characteristics and has not yet deeply evaluated the technical aspects of cybersecurity. This research provides an empirical foundation for the development of a public sector SIA model that can align heterogeneous administration (civil servants and state officials) into a transparent accountability framework.